Focal Brain Lesions and Language Development - J Gordon Millichap (Pediatric Neurology Briefs)
The effects of congenital, unilateral, focal brain lesions on development and hemispheric lateralization of language were investigated in 24 preschool children with hemiplegia followed longitudinally at Stella Marios Scientific Institute, Pisa, Italy.